RESPON RUMAH SAKIT SWASTA SOSIAL KEAGAMAAN TERHADAP ASURANSI SOSIAL: STUDI PENANGANAN KASUS MATERNAL DI RUMAH SAKIT NUR HIDAYAH BANTUL, YOGYAKARTA - Arrus Ferry; Mubasysyir Hasanbasri; Mohammad Hakimi (Journal of Health Service Management, 2016)
Background: The difference between the hospital real cost andthe tariff of INA-CBGs has negative impact on hospital causesfinancial losses, especially private hospital. The potential for thisloss is likely to encourage hospitals to establish a strategy tominimize losses. There are some distortions induced by theprospective payment system i.e. up-coding, cream skimming,readmission, and unbundling. Objective: The aim of this study was to determine Nur Hidayahhospital behaviour in response to INA-CBGs practice inmaternal management. Methods: This study was a quantitative research uses a casestudy approach. Secondary data from medical records, socialinsurance claim documents, records or reports regardingmaternal care and the regulation of social insurance services inthe period of January-June 2014 were use as the data sourcesof this study. Results: There was no evidence to support the practice of upcoding,cream skimming, readmission and unbundling inmaternal care at Nur Hidayah Hospital. Nur Hidayah Hospitalimplemented efficiency strategies and anti-fraud & abuse todeal with social insurance schemes. Conclusion: The INA CBGs-based payment resulted inincreased efficiency of the maternal care in Nur HidayahHospital.